HUBUNGAN KECANDUAN BERMAIN GAME ONLINE PADA SMARTPHONE TERHADAP PRESTASI AKADEMIK SISWA KELAS 12 SMA 1 GERUNG TAHUN 2019 - Sulung Adi Dananjaya; Danang Nur Adiwibawa; Halia Wanadiatri; Dina Qurratu Ainin (Nusantara Hasana Berdikari, 2022)
World Health Organization (WHO) in 2018 classifies addiction playing online game into the International Classification of Disease11th/ ICD-11). Addicted to playing online games is defined as a pattern ofbehavior gaming or playing (